Rancang Bangun Sistem Monitoring dan Notifikasi Pupuk Pada Truckloader Menggunakan Teknik Counter Bebrbasis Internet of Things - Misbach Misbach; Pressa Perdana Surya Saputra (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Truckloader (TL) is a tool that functions to move Fertilizer from the weigher (where the weighing and bagging process is) to the place of the pallet or to the place of the truck bed. Broadly speaking, this tool is in the Bagging 1B unit area. This truckloader has a digital counter, namely a counter which has the function of calculating fertilizer from the weigher to the truckloader. From this counter, this will later be used as a reference or comparison. In order to find out the amount of fertilizer on the pallet or entering the truck body, on the other hand it is also use it for the technician team as a reference for preventive maintenance and replacement of spare parts. So far, counter checking is done manually by visiting the field and seeing it in person. For this, the Internet of Things is needed so that work is more effective and easier for the monitoring process. By using Senesore infrared proximity as input to the Arduino Uno as an electronic circuit controller and running programs, 16x2 LCD as a display of instructions from Arduino, NodeMCU as a liaison between the microcontroller and Ubidots and to display digital data from Arduino. This counter tool will later be used to monitor the amount of fertilizer passing through truckloader via the Ubidots web. This system can display data on Arduino that can be viewed via the Ubidots web that has been made.